Pengembangan Landing Page untuk Mendukung Digitalisasi PT Kosa Group Indonesia Menggunakan Platform Low-Code - Irawan, Arswenda Jameci; Marzal, Jefri; Fadhila Putri, Mutia (Jurusan Sistem Informasi Universitas Islam Negeri Alauddin Makassar, 2025)
This study aims to develop a landing page as part of the digitalization strategy of PT Kosa Group Indonesia, a culinary company consisting of three main divisions: Kosarasa, Kosa Team, and Risafood. The development followed the waterfall method through observation, literature review, system design, implementation, and testing. The Framer platform was selected as a low-code solution due to its efficiency in building responsive, maintainable interfaces without the need for complex programming. This initiative was driven by the limitations of previously used platforms such as LinkTree, which lacked the capability for visual customization and did not effectively unify multi-division information. Performance testing using Google PageSpeed Insights showed an increase from 44 to 54 on mobile and from 44 to 55 on desktop after visual and structural optimizations. Usability testing using the System Usability Scale (SUS) yielded an average score of 87.25, which is categorized as excellent. The results indicate that low-code-based landing page development offers an effective solution to support business digitalization in the culinary sector, while maintaining development efficiency, strong visual identity, and user-friendly experience.